United Kingdom : Financial Sector Assessment Program-Bank Resolution and Crisis Management-Technical Note. (IMF Staff Country Reports; Country Report, 2016)
This paper first describes the architecture for resolution and crisis management. Second, it outlines the resolution policies and operational arrangements currently in place. Third, it discusses the measures taken by the authorities to ensure resolvability. Fourth, it refers to cross-border cooperation issues in resolution. Finally, it describes frameworks for resolution funding and deposit insurance. The U.K. financial safety net is underpinned by strong institutional arrangements. The financial safety net is made up of Her Majesty's Treasury, the Bank of England, the Prudential Regulation Authority, the Financial Conduct Authority, and the Financial Services Compensation Scheme. The authorities are encouraged to continue their efforts to operationalize, test, and refine the crisis preparedness framework, while exploring mechanisms to make it even more robust.